SPIRITUAL INTELLIGENCE IS DIRECTLY PROPORTIONAL TO THE IMPROVEMENT OF SOCIAL ATTITUDES OF ELEMENTARY SCHOOL STUDENTS - Nugroho, Arya Setya; Nursalim, Mochamad; Sujarwanto (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
The formation of a nation can be seen from the people in it who are faithful, pious, intellectual, dignified, and responsible. Educators play a major role in the formation of students in schools towards the development of attitudes and behavior to create a strong nation. Furthermore, if intelligence is formed, it will manifest good attitudes and behavior. With the literature study method, this research will examine spiritual intelligence, social attitudes of elementary school students, and the relevance of spiritual intelligence to the social attitudes of elementary school students. This study is sourced from journals, thesis, internet, theses, dissertations, books, or other relevant sources. In the aspect of spiritual intelligence, it proves to have an effect on the attitudes and behavior of elementary school to university students. There is a need for more specific follow-up research to find out the relevance of spiritual intelligence to the social attitudes of elementary school students.